PERBEDAAN EFEKTIFITAS PEMBERIAN KONSELING PRE OPERATIF DI RUANG RAWAT INAP DAN DI KAMAR OPERASI TERHADAP TINGKAT KECEMASAN, MEAN ARTERI PRESSURE (MAP) DAN HEART RATE (HR) PASIEN SECTIO CAESAREA ANESTESI SPINAL DI SENTRA MEDIKA HOSPITAL MINAHASA UTARA - Suratmi Suprapto; Suci Khasanah; Mariah Ulfah (Jurnal Inovasi Penelitian, 2022)
Sectio caesaria is a way of giving birth to a fetus by making an incision in the uterine wall through the abdominal or vaginal wall or sectio caesaria is a hysterotomy to give birth to a fetus from inside the uterus. Anxiety is a vague and pervasive worry associated with feelings of uncertainty and helplessness. Counseling is a process of providing objective and complete information, carried out systematically with the guidance of interpersonal communication skills, guidance techniques and clinical knowledge that aims to help a person recognize his current condition, the problem he is facing and determine a way out or an effort to overcome the problem. This study aims to determine the difference in the effectiveness of providing preoperative counseling in the inpatient room and in the operating room on the level of anxiety, mean arterial pressure (MAP) and heart rate (HR) for spinal anesthesia patients with spinal anesthesia at the Central Surgical Installation of Sentra Medika Hospital North Minsah. This research method uses a quasi-experimental research type with a non-equivalent control group design. The sampling technique used purposive sampling as many as 20 respondents in each group. Data were taken by measuring the level of anxiety, MAP and HR before and after being given pre operative counseling. The results of the study showed that there was a difference in the effectiveness of providing preoperative counseling in the inpatient room and in the operating room with significant results that preoperative counseling was more effective in the inpatient room than in the operating room with a value on the anxiety level of 0.021 <0.05. At the MAP value, the significant result is 0.021 < 0.05 and the HR value is significant at 0.020 < 0.05. Changes in anxiety levels, MAP and HR can be influenced by the ability of an expert to provide objective information to respondents. Thus the results of this study indicate that the provision of preoperative counseling in the inpatient room will be more effective if it is given when the respondent feels in the inpatient room.